2010
DOI: 10.1111/j.1365-2141.2009.08038.x
|View full text |Cite
|
Sign up to set email alerts
|

Blasts in transient leukaemia in neonates with Down syndrome differentiate into basophil/mast‐cell and megakaryocyte lineages in vitro in association with down‐regulation of truncated form of GATA1

Abstract: 3 SummaryMutations of GATA1, leading to aberrant expression of a truncated form of GATA1 (called GATA1s), are present in transient leukemia (TL) in neonates with Down syndrome. Using these molecular markers of TL, we investigated the growth and differentiation potential of TL blasts in the presence of hematopoietic growth factors (HGFs). Interleukin-3, stem cell factor and granulocyte-macrophage colony-stimulating factor potently stimulated the growth of TL blast progenitors and induced differentiation towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…DS cases are more likely to have B-cell precursor ALL, and their leukemic cells lack adverse genetic abnormalities [24]. Leukemia cells with either i(21q10) or trisomy 21 have the potential for basophil formation [25]. Worth et al [26], has reported a transient leukemic condition in a phenotypically normal newborn bearing i(21q10) clones, suggesting that the q arm of chromosome 21 contains sufficient genetic information for the development of transient leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…DS cases are more likely to have B-cell precursor ALL, and their leukemic cells lack adverse genetic abnormalities [24]. Leukemia cells with either i(21q10) or trisomy 21 have the potential for basophil formation [25]. Worth et al [26], has reported a transient leukemic condition in a phenotypically normal newborn bearing i(21q10) clones, suggesting that the q arm of chromosome 21 contains sufficient genetic information for the development of transient leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…3a), and into megakaryocytes in the presence of thrombopoietin (TPO) (Fig. 3b), by demonstrating that the differentiated cells that appeared after culture carried the same GATA1 mutations as the TL blasts did before culture (Miyauchi et al, 2010) (see section 4.2). Consistent with these in vitro data, massive increase of basophils in the peripheral blood of a patient with TL has been reported (Worth et al, 1999) and another case demonstrating pericardial effusion containing predominantly basophils has been described (Zipursky et al, 1997).…”
Section: Differentiation Capability Of Leukemic Blastsmentioning
confidence: 99%
“…The differentiation capability of TL blasts into mature blood cells is unique for AML and might be somehow associated with the spontaneous remission of this disorder. Although TL blasts express some markers of the erythroid lineage and, in fact, erythroblasts at various stages of differentiation appeared in culture of TL blasts in the presence of erythropoietin and SCF in combination, these cells expressed full-length GATA1 but not aberrant GATA1s protein (see section 4.2) and, therefore, it was shown that these differentiated erythroid cells were derived from coexisting normal erythroid progenitors (Miyauchi et al, 2010). …”
Section: Differentiation Capability Of Leukemic Blastsmentioning
confidence: 99%
See 2 more Smart Citations